Pengendalian Hama Kutu Putih (Bemisa Tabaci) pada Buah Sirsak dengan Menggunakan Pestisida Nabati Ektrak Serai (Cymbopogon Nardus L.) - Fahruddin Arfianto (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Pesticides are chemical compounds that are structured to control pests and diseases that attack plants. In Indonesia, pesticides are often used to control pests and diseases that attack plants, but at this time, from pesticides are found many residues, especially in plants and soil causing environmental pollution, especially chemical pesticides. Nabati pesticides are pesticides used for controlling pest and disease for plants made from natural ingredients such as essential oils produced by plants. Nabati pesticides have several advantages such as easily decomposes by sunlight andit does not cause an environmental disturbance. The purpose of this research is 1)To know how to make nabati pesticides 2) To find out how many doses of nabati pesticides are used. The method used in this research is a direct application of crops affected by pests. In two treatments with different doses proved that with a mixing dose of 50 ml of serai extract with 500 ml water was more effective in controlling pests that attacked soursop.